Impact of the COVID-19 Pandemic on Patient- and Family-Centered Care and on the Mental Health of Health Care Workers, Patients, and Families - Lessa, Alessandra Rodrigues Dias; Bitercourt, Victória Noremberg; Crestani, Francielly; Andrade, Gabriela Rupp Hanzen; Costa, Caroline Abud Drumond; Garcia, Pedro Celiny Ramos (Frontiers in Pediatrics, 2022)
During the COVID-19 pandemic, hospitals around the world were forced to reorganize their processes in an attempt to contain the spread of the virus while still providing adequate care to patients. In the Pediatric Intensive Care Unit (PICU) setting, changes in family visitation protocols and restrictions on parent chaperones during hospitalization, as well as other changes, interfered with care. Based on a narrative review of the literature, supported by the authors’ observations in practice, we aimed to describe the impact of the pandemic on patient and family-centered care (PFCC) in the PICU environment, especially regarding the presence of family members, family support, and communication with patients and their families, as well as the effects of changes in these practices on the mental health of those involved. In this context, several strategies were used to sustain PFCC, and, despite many challenges, attempts were made to achieve the bare-minimum goals of humanized care for patients, families, and providers alike.